Memory, body and dance: a review of literature - Cleave, Peter (Te Kaharoa, 2014)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Distinguishing dance from movement may be a matter of state of mind, of invested meaning. Dance in English seems easy to define but when we get to phrases like ’the dance of desire’ or ’we were lead on a merry dance’ and when we try and untangle dance from stance or, in some cases, trance and the dance of an eyebrow or a look we need to carefully describe what is going on.